2018
DOI: 10.1002/cam4.1714
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated miR‐144‐3p contributes to progression of lung adenocarcinoma through elevating the expression of EZH2

Abstract: ObjectivesThe intention of our study was to investigate the relationship between miR‐144‐3p and EZH2 as well as the effects of their interaction on cell propagation and invasiveness in lung adenocarcinoma (LUAD).MethodsThe expression levels of miR‐144‐3p and EZH2 in LUAD tissues and normal tissues were determined by qRT‐PCR. The dual‐luciferase reporter assay was utilized to validate the targeting relationship between miR‐144‐3p and EZH2. MTT assay and colony formation assay were performed to evaluate the viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…Recent years, the expression status and biological function of miR-144-3p have been intensively investigated in many cancers [9,[20][21][22]. However, previous studies have produced inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years, the expression status and biological function of miR-144-3p have been intensively investigated in many cancers [9,[20][21][22]. However, previous studies have produced inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yin reported that miR-144-3p is downregulated in breast cancer and functions as a tumor suppressor through repressing CEP55 [9]. Liu et al showed that the expression of miR-144-3p is decreased in lung adenocarcinoma (LUAD) tissues, and overexpression of miR-144-3p inhibited propagation and invasiveness of LUAD cells [20]. In contrast, other groups reported that miR-144-3p is upregulated in the specimens of nasopharyngeal carcinoma and clear cell renal cell carcinoma and serves as an onco-miRNA [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In LUAD, oncogenic networks and oncogenes guided by miR-143 were identified and may help with tumor suppressor effects, establish new prognostic indicators, and find therapeutic targets [17]. The propagation, migration, and invasion of LUAD cells are obstructed by overexpression of the miR-144 family target, EZH2 [18]. These studies all indicate that miRNAs in the ceRNA network may act as suppressors in LUAD.…”
Section: Discussionmentioning
confidence: 94%
“…MiR-144-5p increased the radiosensitivity of NSCLC cells by repressing activating transcription factor 2 (ATF2) [45] and miR-451a decreased doxorubicin resistance in lung cancer via suppressing c-Myc [46]. MiR-144-3p and MiR-30a-3p inhibited the progression of lung cancer via targeting EZH2 and DNA methyltransferase 3a [47,48]. Long noncoding RNA RMRP sponged miR-1-3p to promote NSCLC cell proliferation and invasion [49].…”
Section: Discussionmentioning
confidence: 99%